2014
DOI: 10.1007/s00122-014-2363-2
|View full text |Cite
|
Sign up to set email alerts
|

A major QTL associated with Fusarium oxysporum race 1 resistance identified in genetic populations derived from closely related watermelon lines using selective genotyping and genotyping-by-sequencing for SNP discovery

Abstract: A major quantitative trait locus (QTL) for Fusarium oxysporum Fr. f. sp. niveum race 1 resistance was identified by employing a "selective genotyping" approach together with genotyping-by-sequencing technology to identify QTLs and single nucleotide polymorphisms associated with the resistance among closely related watermelon genotypes. Fusarium wilt is a major disease of watermelon caused by the soil-borne fungus Fusarium oxysporum Schlechtend.:Fr. f. sp. niveum (E.F. Sm.) W.C. Snyder & H.N. Hans (Fon). In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 32 publications
1
29
2
Order By: Relevance
“…The number of tags (933,662) generated in this study with ApeKI restriction enzyme exceeded those generated (527,844 tags) with the same enzyme in an elite by elite F 2 watermelon population described by Lambel et al (2014). Due to the low genetic diver- sity among cultivated watermelon (Levi et al, 2001), the number of usable SNPs (1024) generated in the current study was small compared to that reported for other crops such as rice (>30,000) (Spindel et al, 2013) and wheat (>130,000) (Rutkoski et al, 2013) using GBS.…”
Section: Genotyping By Sequencing and Snp Analysismentioning
confidence: 90%
See 4 more Smart Citations
“…The number of tags (933,662) generated in this study with ApeKI restriction enzyme exceeded those generated (527,844 tags) with the same enzyme in an elite by elite F 2 watermelon population described by Lambel et al (2014). Due to the low genetic diver- sity among cultivated watermelon (Levi et al, 2001), the number of usable SNPs (1024) generated in the current study was small compared to that reported for other crops such as rice (>30,000) (Spindel et al, 2013) and wheat (>130,000) (Rutkoski et al, 2013) using GBS.…”
Section: Genotyping By Sequencing and Snp Analysismentioning
confidence: 90%
“…The difference in disease severity observed in the F 1 in this study and previously published work might have resulted from a variation in the inoculation method and soil type used. In the current study, a modified-tray dip method was used for inoculation in sand: peat: vermiculite medium while in most studies, the root dip method and various combinations of sand, soil, peat and vermiculite are used (Dane et al, 1998;Freeman and Rodriguez, 1993;Hawkins et al, 2001;Lambel et al, 2014;Martyn and McLaughlin, 1983;Martyn and Netzer, 1991;Yetisir et al, 2003;Everts, 2004, 2007;Zhou et al, 2010). These results show that researchers should carefully consider the time (DAI) of data collection and the method of inoculation used when drawing conclusions from genetic studies of Fon.…”
Section: Phenotypic Analysismentioning
confidence: 99%
See 3 more Smart Citations